Personality Factors and their Impact in creating bullying behavior in the workplace: An Empirical Study on the administrative staff at the University of King Abdul-Aaziz - Al Mudeel, Sita Bint Al Mudeel; Al Selmi, Rabab bint mohammed; Al Shamasi, Areej; Zaki, Khadija bint Mahmoud (Journal of Economic, Administrative and Legal Sciences, 2018)
This study has addressed the subject of personality features and their effect on the existence of bullying in the work place. The main point of the research is defining how personal features may create an intimidating environment for some staff at the King Abdul-Aziz University. It has also showed the extent of the bullying behavior at the King Abdul-Aziz University staff. In addition, the study discovers the effect of the five major elements that define the personality in developing the bullying habit in the work place. The researcher depended on the analytical descriptive method to identify the personal features and their effects on the existence of bullying within the work environment. Questions were used on a survey to collect studies’ data. The researcher concluded that a statistical relationship between anger and bullying in the work place was founded according to the study. Another statistical relationship was founded between the individual acceptability and bullying. Furthermore, a statistical relationship was spotted between clear consciences and bullying in the work place. A safe environment for staff was recommended by the researcher to support productivity. The study shows that developing the skills of staff and providing workshops and improvement courses would result in enhancing their personalities. Also, better awareness of the bullying concept in the work place and the destructive effects on staff members, which would result in the unsuitability of the work place environment. In addition, applying anti-bullying policies and never undermine it. The study recommend that more administrative and psychological studies about this phenomenon are needed such as its relativeness to corporate culture, and leadership styles.